Research on Metal Mesh Coupling Mirrors Utilizing Metasurfaces for Optically Pumped Gas THz Lasers - Lijie Geng; Zhenxiang Fu; Shuaifei Song; Chenglong Bi; Wenyan Zhang; Ruiliang Zhang; Kun Yang; Yanchen Qu (Photonics)
Optically pumped gas terahertz (THz) lasers (OPGTLs) as reliable sources of THz radiation have been extensively utilized within THz application areas. In this paper, a substrate-free metal mesh coupler based on the metasurfaces principle was designed for continuous wave OPGTL, which is suitable for the Fabry–Perot (FP) THz resonator. The parameters of substrate-free metal mesh are calculated by the Ulrich equivalent circuit model, and the influence of metal mesh period and linewidth on its transmittance is analyzed quantitatively. Taking the THz laser with the 118.8 µm of CH3OH optically pumped by the 9.6 µm CO2 laser line for instance, two kinds of metal mesh were devised as input and output couplers of the resonator, and the transmittance and reflectance of the metal meshes are verified by the finite-difference time-domain (FDTD) method. Furthermore, the transmitted and reflected light fields of the FP resonant cavity metal mesh mirrors were simulated by using the FDTD method under the vertical incidence of both pump light and THz waves. Validation of the optical field characteristics of the substrate-free metal meshes confirmed their suitability as ideal input and output coupling cavity mirrors for FP resonant cavities in optically pumped gas THz lasers.